Telewizyjna prognoza pogody – analiza gatunku z perspektywy diachronicznej - MAC, AGNIESZKA (Stylistyka, 2024)
The article attempts to examine genre changes within the genre pattern of the weather forecast. In the first part, I propose a categorisation of the weather forecast as a text genre, mainly focusing on its television variant. Thereby, I point out pertinent research in the Polish and German literature for the reasons of comparison. I continue by outlining the assumptions of multimodal text analysis that I have used n my investigation of the television weather forecast, highlighting the fact that it represents an audiovisual text in which meaning is constructed through the conceptual combination of semiotic devices present in it. In the second part, I present the results of my analysis of a particular weather forecast broadcast on Channel TVP 1 after the main edition of the news. I describe the modifications to its design for over the past 30 years and demonstrate the phases of the pattern transformation starting at the beginning of the 1990s and reaching the forms of expression nowadays. Based on the comparison, I attempt to answer the question of how media texts in general, and television weather forecast in particular, have changed over the period of time I have focused on. The conclusions summarise the research results obtained and indicate the reasons for the genre changes taking place.